Chasing unicorns: The European single safe asset project. (April 2018) - Gabor, Daniela; Vestergaard, Jakob
For the past 20 years, Economic and Monetary Union (EMU) institutions have sought to engineer a single safe asset that would provide a credible store of value for capital market participants. Before 2008, the European Central Bank used shadow banking to create a single safe asset that we term shadow money, and in doing so also erased borders between Euro area government bond markets. Lacking appropriate ECB support, shadow euros could not withstand the pressures of the global financial crisis and brought down several periphery euro government bonds with them. Two new plans, the Capital Markets Union and the Sovereign Bond-Backed Securities, again turn to shadow banking, this time by using securitization to generate an entirely private safe asset or a public–private safe asset. Such plans cannot solve the enduring predicament of EMU's bond markets architecture: that Member States have competed for investors (liquidity) since the introduction of the euro, betraying a deep hostility towards collective political solutions to the single safe asset problem. Technocratic-led, market-based initiatives need to persuade EMU states that there is little threat to their ability to issue debt in liquid markets. Without ECB interventions, market-based engineering of single safe assets runs the danger of repeatedly destabilizing national bond markets.